The Protective Effect of Polyherbal Formulation, Harak Formula, on UVA-Induced Photoaging of Human Dermal Fibroblasts and Mouse Skin via Promoting Nrf2-Regulated Antioxidant Defense - Lohakul, Jinapath; Chaiprasongsuk, Anyamanee; Jeayeng, Saowanee; Saelim, Malinee; Muanjumpon, Phetthinee; Thanachaiphiwat, Saowalak; Tripatara, Pinpat; Soontrapa, Kittipong; Lumlerdkij, Natchagorn; Akarasereenont, Pravit; Panich, Uraiwan (Frontiers in Pharmacology, 2021)
Polyherbal formulation combining multiple herbs is suggested to achieve enhanced therapeutic effects and reduce toxicity. Harak herbal formula (HRF) extracts were proposed to regulate skin responses to UVR through their ability to suppress UVA-induced matrix metalloproteinase-1 (MMP-1) and pigmentation via promoting antioxidant defenses in in vitro models. Therefore, natural products targeting Nrf2 (nuclear factor erythroid 2-related factor 2)-regulated antioxidant response might represent promising anti-photoaging candidates. Hesperetin (HSP) was suggested as a putative bioactive compound of the HRF, as previously shown by its chemical profiling using the liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (LC-QTOF-MS). In this study, we explored the anti-photoaging effects of HRF extracts and HSP on normal human dermal fibroblasts (NHDFs) and mouse skin exposed to UVA irradiation. Pretreatment of NHDFs with HRF extracts and HSP protected against UVA (8 J/cm2)-mediated cytotoxicity and reactive oxygen species (ROS) formation. The HRF and HSP pretreatment also attenuated the UVA-induced MMP-1 activity and collagen depletion concomitant with an upregulation of Nrf2 activity and its downstream genes (GST and NQO-1). Moreover, our findings provided the in vivo relevance to the in vitro anti-photoaging effects of HRF as topical application of the extracts (10, 30 and 100 mg/cm2) and HSP (0.3, 1, and 3 mg/cm2) 1 h before UVA exposure 3 times per week for 2 weeks (a total dose of 60 J/cm2) mitigated MMP-1 upregulation, collagen loss in correlation with enhanced Nrf2 nuclear accumulation and its target protein GST and NQO-1 as well as reduced 8-hydroxy-2'-deoxyguanosine (8-OHdG) in irradiated mouse skin. Thus, our findings revealed that HRF extracts and HSP attenuated UVA-induced photoaging via upregulating Nrf2, together with their abilities to reduce ROS formation and oxidative damage. Our study concluded that the HRF and its bioactive ingredient HSP may represent potential candidates for preventing UVA-induced photoaging via restoration of redox balance.